Organizational learning and organizational effectiveness: a brief insight / Azfahanee Zakaria and Syed Mohammed Alhady - Zakaria, Azfahanee; Alhady, Syed Mohammed (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Today’s business environment is changing faster than ever. The rapid technological change and increase demand of knowledgeable customers have forced the organizational leaders to think outside the box in aligning their products and services as such. The changes in the business environment have created greater competition among business owners and this has led to continuous innovation and invention.